Kreativitas Gerak dan Lagu Sebagai Media Pembelajaran Anak Usia Dini di RA Al-Mahabbah - Yusnita, Novi Cynthia; Afdhalina; Kharida Shaleha (Outline Publisher, 2024)
Creativity is very necessary in children's development because it will influence the working of the right brain to develop an independent, confident and productive personality. However, in reality there are still ways or methods used by teachers that do not attract children's interest in learning in class. Usually, children learn to focus on books or explanations given by the teacher. This will of course make children quickly bored with learning. The method used during service activities is to use demonstrations and questions and answers with children. The results obtained are that children become more enthusiastic about learning children also have new knowledge about body parts in English. So, it can be concluded that the implementation of learning movements and songs to develop children's creativity includes three things that are carried out, the first is the initial activity, the second is the core activity, the third is the final activity, then the teacher gives examples of movements according to song lyrics to develop children's creativity. This succeeded in creating a pleasant learning atmosphere so that children were enthusiastic about participating in class learning.